Effects of Massa Medicata Fermentata on the intestinal pathogenic flagella bacteria and visceral hypersensitivity in rats with irritable bowel syndrome - Zhuang, Zhaomeng; Huang, Chen; Zhang, Yiguang; Lv, Bin (Frontiers in Physiology, 2022)
Objective: To investigate the effect of Massa Medicata Fermentata (MMF) on the changes of pathogenic flagellar bacteria and visceral hypersensitivity in rats with diarrhea irritable bowel syndrome (IBS-D). Methods: Thirty adult SD rats were randomly divided into normal control group (n = 10), model control group (n = 10), and MMF group (n = 10). Acetic acid enema combined with restraint stress was used to build the IBS-D visceral hypersensitivity model; Abdominal withdrawal reflex (AWR) test was used to assess the visceral sensitivity of rats; 16SrRNA sequencing was used to analyze the changes of intestinal bacteria in each group, and the content of pathogenic flagellated bacteria were quantitatively counted; The content of flagellin in colonic mucosa was detected by ELISA; TLR5 protein in colonic mucosa of rats was detected by Western Blot. Results: After IBS-D modeling, the visceral sensitivity of rats was significantly higher in the model control group than that in the normal control group (p = 0.0061), while it was significantly decreased in MMF group compared with the model control group (p = 0.0217), but without significant difference compared with the normal control group (p = 0.6851). The number of fecal Bifidobacterium and Lactobacillus in the model group were significantly decreased compared with the normal control group (p < 0.0001); While they were significantly increased in the MMF group compared with the model control group and normal control group (p = 0.009; p < 0.0001). The amount of fecal pathogenic flagellated bacteria in the model group was significantly increased compared with the normal control group (p = 0.001); However it was significantly reduced in MMF group compared with the model group (p = 0.026), which has no statistically difference with the normal control group (p = 0.6486). The content of flagellin in colonic mucosa was significantly increased in the model group when compared with the normal control group (p < 0.0001), and it was decreased in MMF group compared with the normal control group (p < 0.0001), but there was no statistical difference with the normal control group (p = 0.6545). The expression level of TLR5 protein in colonic mucosa of rat was significantly increased in model control group compared with the normal control group (p = 0.0034), However, it was significantly decreased in MMF group compared with normal control group (p = 0.0019), but it was no statistical difference with the normal control group (p = 0.7519). Conclusion: MMF can reduce visceral hypersensitivity by decreasing the content of pathogenic flagellated bacteria and their flagellin and inhibiting its specific receptor TLR5 protein expression in colonic mucosa in IBS-D rats.